2015
DOI: 10.1890/14-0839.1
|View full text |Cite
|
Sign up to set email alerts
|

Trophic mismatch requires seasonal heterogeneity of warming

Abstract: Abstract. Climate warming has been shown to advance the phenology of species. Asynchronous changes in phenology between interacting species may disrupt feeding interactions (phenological mismatch), which could have tremendous consequences for ecosystem functioning. Long-term field observations have suggested asynchronous shifts in phenology with warming, whereas experimental studies have not been conclusive. Using proxy-based modeling of three trophic levels (algae, herbivores, and fish), we show that asynchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…This spatial and temporal heterogeneity can, in turn, impose contrasting selection pressures that are difficult for populations to reconcile on short time scales (Senner et al 2017). Our results add to the growing body of literature highlighting the importance of asynchronous climate change regimes (Visser et al 1998, Both et al 2006, Straile et al 2015, Senner et al 2017) by revealing that they occur across much of North and Central America and may be an important mediator of gene flow. Given that asynchronous regimes are rarely incorporated into predictive models of potential biotic responses to climate change, our findings suggest the need to reconsider the selective pressures that underlie these theoretical frameworks.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This spatial and temporal heterogeneity can, in turn, impose contrasting selection pressures that are difficult for populations to reconcile on short time scales (Senner et al 2017). Our results add to the growing body of literature highlighting the importance of asynchronous climate change regimes (Visser et al 1998, Both et al 2006, Straile et al 2015, Senner et al 2017) by revealing that they occur across much of North and Central America and may be an important mediator of gene flow. Given that asynchronous regimes are rarely incorporated into predictive models of potential biotic responses to climate change, our findings suggest the need to reconsider the selective pressures that underlie these theoretical frameworks.…”
Section: Discussionmentioning
confidence: 62%
“…Unlike spatially asynchronous dynamics, which can increase the persistence of meta-populations (Heino et al 1997), asynchronous climate change regimes are temporally asynchronous and can therefore impose contrasting selection pressures to which populations have difficulty responding (Senner et al 2017). Accordingly, recent empirical work has demonstrated that asynchronous regimes can adversely affect many species (Straile et al 2015), limiting the ability of some populations to respond to climatic changes (Both and Visser 2001) and causing intra-specific variation in vulnerability to climate change (Visser et al 2003) that leads to local population declines (Both et al 2006). As such, asynchronous regimes represent a frequently overlooked, but critical component of global climate change that should be incorporated into climate-related predictive frameworks.…”
Section: Review and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, the growth and survival of young fish is a function of both temperature and prey availability [20,72]. Shifts in the timing of spawning events could result in a trophic mismatch of prey availability and demand during early life history events for fish [73,74], but such a phenomenon requires heterogeneity in seasonal warming rates [75]. The differences in warming rates between high-elevation SRM streams [31] and those reported for SRM lakes in this study indicate heterogeneity in warming rates and therefore, the potential for climate driven trophic mismatches during early fish life history.…”
Section: Discussionmentioning
confidence: 99%
“…The environment experienced by this population also differs from that of others in that temperatures have increased more during late than early spring (Visser et al ) something not found in our study. Thus, both increasing spring temperatures per se and the temporal pattern of temperature change over the spring months are important for predicting the response of, and consequences for, a population (Laaksonen et al , Straile et al ). The specific temporal pattern of warming over the spring months may consequently either result in a mismatch between trophic levels, maintained synchrony or even increased synchrony if there was a mismatch between the two trophic levels before the temperature changed (Jonzén et al , Vatka et al , Visser et al ).…”
Section: Discussionmentioning
confidence: 99%